Design and Evaluation of the User Interface of the Hala Sultan Tekke Multimedia Application - Pouyioutas, Philippos; Paschali, Paschalis; Laghos, Andrew (My University, 2008)
This paper presents the user interface of the Hala Sultan Tekke application. The paper addresses the design considerations taken into account at the time the interface was developed. It then presents an evaluation of the interface by students. The application was presented to the students during a class. The students then had a chance to use it themselves during the class and also after that, on their own time. The feedback of the students with regards to the user interface was collected through a questionnaire which assisted us in identifying the strengths and weakness of the application, but also gave us useful suggestions for future updates.
Keywords: Students